Grain trade and market integration in China’s Qing dynasty - Li, Jianan (2014)
The paradox of China’s failure to industrialize despite its thriving commercialization before the 19th century has been debated intensively, especially in terms of whether market efficiency is sufficient for industrialization in the pre-modern period. This thesis sheds light on this question using archival data on grain prices covering Qing China’s most prosperous episode (1740-1820) to identify the determinants of market evolution as well as the true extent of market integration. My results suggest that China’s market efficiency on the eve of Western industrialization has been grossly overstated, and further imply that China’s market was heavily influenced by its bureaucratic structure. My analysis is based on a historical dataset of monthly grain prices (rice, wheat) in 211 prefectures across China and I match these with new data on the physical geography of the postal and river network and physiographic distribution. My analysis first confirms the close relationship between market integration and geographic proximity but shows that geographical influence is dominated by provincial boundaries. I then employ novel panel time series methods to account for the impact of local and global shocks and to investigate the evolving process of market integration over time. This analysis indicates that China experienced continuous market disintegration with fragmentation driven by political structure. These results support my hypothesis that Qing China’s political system was not conducive to the development of the market mechanism since its primary concern was market regulation rather than revenue.